Total Hip Arthroplasty: MR Imaging of Complications Unrelated to Metal Wear - Burge, Alissa J. (Seminars in Musculoskeletal Radiology, 2015)
Hip arthroplasty is one of the most common and successful orthopedic procedures performed for the treatment of advanced osteoarthritis. Due to the high prevalence of these implants within the population, complications related to hip arthroplasty are commonly encountered by clinicians and radiologists alike. Knowledge of the diagnostic imaging options available for evaluation of these implants, as well as of the expected range of normal and pathologic findings following hip arthroplasty, is crucial in allowing the radiologist to formulate an appropriate imaging strategy and accurately interpret the subsequent imaging findings.
Keywords: hip; arthroplasty; complications